Adsorption kinetics of n-propanol on platinized platinum electrode in sulphuric acid solution - Fugivara, Cecilio Sadao [UNESP]; Sumodjo, P. T A; Rabockai, T. (Elsevier B.V., 1989)
the adsorption kinetics of n-propanol on platinized platinum electrode in sulphuric acid solution is studied. Data on the influence of adsorption potential and of temperature are given. Values for the velocity constants and for activation energies are evaluated from the experimental data. © 1989.